2013
DOI: 10.1111/1574-6968.12161
|View full text |Cite
|
Sign up to set email alerts
|

On-farm biopurification systems: role of white rot fungi in depuration of pesticide-containing wastewaters

Abstract: Environmental contamination with pesticides is an undesired consequence of agricultural activities. Biopurification systems (BPS) comprise a novel strategy to degrade pesticides from contaminated wastewaters, consisting of a highly active biological mixture confined in a container or excavation. The design of BPS promotes microbial activity, in particular by white rot fungi (WRF). Due to their physiological features, specifically the production of highly unspecific ligninolytic enzymes and some intracellular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(13 citation statements)
references
References 78 publications
0
13
0
Order By: Relevance
“…Majority of the studies have demonstrated the bioremediation potential of white-rot fungi; Phanerochaete chysosporium, Trametes versicolor, Bjerkandera adjusta and Pleurotus sp., by virtue of producing different ligninolytic enzymes such as laccases and peroxidases [19]. The ligninolytic enzymes from white-rot fungi have been applied for transformation of variety of organic pollutants such as pesticides from contaminated wastewaters by promoting microbial activity using a biopurification system (BPS) [20]. Owing to restricted access of ligninolytic enzymes to lignin granules which are deposited on the surface of lignocellulosic fibres, pressure refining was applied for separation of fibres of lignocellulosic materials.…”
Section: White-rot Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Majority of the studies have demonstrated the bioremediation potential of white-rot fungi; Phanerochaete chysosporium, Trametes versicolor, Bjerkandera adjusta and Pleurotus sp., by virtue of producing different ligninolytic enzymes such as laccases and peroxidases [19]. The ligninolytic enzymes from white-rot fungi have been applied for transformation of variety of organic pollutants such as pesticides from contaminated wastewaters by promoting microbial activity using a biopurification system (BPS) [20]. Owing to restricted access of ligninolytic enzymes to lignin granules which are deposited on the surface of lignocellulosic fibres, pressure refining was applied for separation of fibres of lignocellulosic materials.…”
Section: White-rot Fungimentioning
confidence: 99%
“…Bioremediation of benzo[a]pyrene under nutrient sufficient (ligninolytic) culture conditions resulted in up-regulation of PAH oxidizing monooxygeneses with concomitant formation of P450-hydroxylated metabolite which was further removed during subsequent non-ligninolytic phase. Importance of another novel strategy based on biopurification systems in promoting bioremediation of pesticides containing wastewaters by means of highly active biological mixture, in particular white-rot fungi was highlighted in a review by Rodríguez-Rodríguez et al [20]. The sustainability and environment friendly nature of bioremediation was displayed in the bioremediation of sewage sludge from sewage treatment plant with mixed filamentous inoculum in a large-scale bioreactor by employing a continuous process [130].…”
Section: Technological Advances In Fungal Bioremediationmentioning
confidence: 99%
“…Moreover, WRF synthesize intracellular cytochrome P-450 monooxygenase, which intensifies their potential for degradation. Biotransformation of pharmaceuticals by WRF using the cytochrome P-450 system is similar to biotransformation by higher animals (Pointing 2001;MarcoUrrea et al 2010a, b, c;Rodriguez-Rodriguez et al 2013). PNSAID oxidation by this enzyme system leads to a new intermediate, mainly with the hydroxyl group.…”
Section: Introductionmentioning
confidence: 98%
“…1.9, 10.5 and 28.3 days were calculated as the half-lives of 2,4-D, MCPP and dicamba, respectively. Rodriguez-Rodriguez et al (2013) studied the white rot fungi for depuration of pesticides due to their physiological features, intercellular enzymatic complexes and highly unspecific ligninolytic enzymes. Jilani (2013) isolated Pseudomonas identified as IES-Ps-1 from soil for studying on biodegradation of pesticides.…”
Section: Biodegradation Terpenes Like Eucalyptus Leavesmentioning
confidence: 99%